How Brexit affects Least Developed Countries - Zoryana Olekseyuk; Israel Osorio Rodarte (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
Following the decision of the British referendum on 23 June 2016, the United Kingdom (UK) plans to exit the European Union (EU). Article 50 of the Lisbon Treaty was invoked at the end of March 2017 and the UK will officially leave the single market and customs union in March 2019. Brexit negotiations have proven difficult due to diverging positions of the two partners on many issues, such as freedom of movement, financial contributions and the potential re-emergence of a tough border between the Republic of Ireland and Northern Ireland. Despite the successfully negotiated Withdrawal Agreement and Political Declaration, there is still con¬siderable political uncertainty about the final EU-UK deal. Regardless of the final outcome of the negotiations, Brexit implies fundamental changes in the British trade regime concerning third countries. This starts with a negotiation of national terms of access for World Trade Organization (WTO) membership and extends to renegotiation of the numerous EU free trade agreements. Moreover, the UK will no longer be part of the European Generalised Scheme of Preferences (GSP) or the Everything But Arms (EBA) treaty, which allow vulnerable developing countries to pay fewer or no duties on their exports to the EU. The Economic Partnership Agree-ments (EPAs) between the EU and African, Caribbean and Pacific countries will not apply to the UK either. While the negative effects of Brexit on the UK and EU are in the limelight, the implications for third countries receive less attention. This paper puts the spotlight on these often-overlooked issues by presenting new findings on Brexit implications for Least Developed Countries (LDCs) and discussing policy recommendations. Developing countries with close ties to the UK will suffer from Brexit as import duties are once again imposed. In particular, 49 of the world's poorest countries presently benefit from preferential treatment that covers 99% of all products under the EBA agreement. Although these countries account for only 1.15% of the UK's imports, the share of their exports to the UK exceeds 35% in apparel, 21% in textiles and 9% in sugar (calculations based on the UN Comtrade data for 2013-2015). Our findings show that losing these preferences together with the UK's withdrawal from the EU may cause EBA countries' GDPs to fall by -0.01% to -1.08%. Our simulations also indicate that the highest losses will occur in Cambodia and Malawi, where dependence on the UK market is strong. Moreover, Brexit may cause the number of those living in extreme poverty (PPP 1.90 a day) to rise by nearly 1.7 million in all EBA countries. These are conservative estimates of Brexit's negative impacts; they do not take into account the addi¬tional implications of uncertainty, depreciation of the pound sterling, reduced aid spending, remittances and investments. The UK must act to mitigate the adverse effects on economically vulnerable countries. Such action may include replicating existing EU treaties that grant preferential access to goods from LDCs, creating a more development-friendly UK trade policy with preferential access to services imports and cumulative rules of origin, as well as offering better-targeted aid for trade initiatives. The EU could also support LDCs by implementing liberal cumulative rules of origin and applying its preferential treatment partly to goods with a low value-added content from considered countries. In addition, developing countries should diversify their export destinations and industries as well as engage in economic transformation that makes them less dependent on UK trade, aid and foreign direct investment (FDI).
Keywords: 330; Handel und Investitionen; Regionale + globale + transnationale Governance